Prototipe Sistem Monitoring Konsumsi Energi Listrik serta Estimasi Biaya pada Peralatan Rumah Tangga Berbasis Internet Of Things - Nursamsi Adiwiranto, Mohamad; Budi Waluyo, Catur (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2021)
Electricity has become a basic necessity for everyone. Household appliances using electricity have become a basic human need today. Monitoring equipment is needed to know how much power, energy, used and the estimated cost to be paid. The tool designed for this monitoring system uses a PZEM-004T sensor, the platform Ubidots and NodeMCU. The PZEM-004T sensor functions to measure the voltage, current, power, power factor, and energy contained in electrical loads. And NodeMCU is needed as a microcontroller. The results can be displayed on the platform Ubidots and the 16x2 LCD used. The test results obtained through measurements using the PZEM-004T sensor for designing a prototype energy monitoring system have a voltage accuracy value of 98.94%, 99.18% current, 98.87% power, 98.44% power factor, and 97 electrical energy consumption. , 89%. In household electrical appliances (led lights, televisions, fans, ricecookers, and laptop chargers) the results of electrical energy consumption in a month are 43.56 kWh and the estimated cost is Rp 114.781.52.